The Impact of Digitalization on Traditional Handicraft Markets Among the Toraja Community - Yusrijal, Yusrijal; Aliyan, Lisana Sidqin; Rina, Rina (Journal Social Civilecial, 2025)
Digitalization is explored as an area of interest concerning its effects on changing the traditional handicraft market in which the Toraja community operates in terms of economic potential, cultural core values as well as social relations. The usage of digital tools in increasing the opportunities of the market for Toraja artisans’ results in higher livelihoods as well as investments on the community. Still, there is a flip side of it, which refers to issues of cultural significance, since the artisans have had to alter the more local, cultural connotations of their art, to suit international markets. This paper fills the existing literature by discussing how information access influence’s cultural identity maintenance and pointing to the economic inequity resulting from the unequal distribution of digital resources and skills. Moreover, new generations of artisans joined handicraft business, thus, combining generations knowledge and experience with masterpieces of outstanding technologies. Such dynamics point to the need for a equilibrium between market needs and cultural values in a given society in as the artisans adapt to the digital markets. Participants were sampled through cultural probes followed by fortnightly interviews with the artisans, giving the study rich data regarding digitalisation, culture and community transformation. The study indicates that if individuals and indigenous cultures learn modern practices of Using the digital interfaces and the market fairness, digitization contributes positively towards the economic sustainability and cultural retention within the traditional society.